Reading Engineers Concept of Justice: The Real Power Hermeneutical Consciousness (A Gadamerâs Philosophical Hermeneutics) - Noor, Nina Mariani (DINIKA : Academic Journal of Islamic Studies, 2016)
This paper aims to describe the concept of justice in Islam interpreted by Ali Asghar Engineer by using Gadamerâs philosophical hermeneutics. Gadamerâs philosophical hermeneutics is ontological rather than methodological and it has been very influential in interpretation world. Engineerâs work in interpreting the concept of justice in Islam, in the notion of Gadamerâs philosophical hermeneutics, is affected by his horizon and fusion of horizons. His prejudices into the world lead him to bring about the idea of liberation by doing liberative interpretation. It is hoped that his liberative interpretation will influence Muslimsâ way of thinking and gradually can challenge the structures of modern oppressions so that people will live in justice and peace. Since all Engineerâs efforts to interpret Qurâan and hadiths in liberative spirit are initiated by his question into the world, it means that he showsÂ  his ability to see what is questionable which is the real power of hermeneutical consciousness. This paper attempts to present the basic concepts of Gadamerâs philosophical hermeneutics then use them to analyze the interpretation on justice made by Engineer based on his liberative idea.Â Keywords: Justice, Hermeneutical Consciousness